STRATEGI GURU DALAM MENGAJAR SESUAI DENGAN GAYA BELAJAR PESERTA DIDIK - Paridon, Paridon; Mahmud, Salami (Information Technology and Science (ITScience), 2025)
The success of the learning process largely depends on teachers’ ability to understand and adapt their teaching strategies to students’ learning styles, particularly at MIN 12 Nagan Raya. This article examines three primary learning styles—visual, auditory, and kinesthetic—which reflect students’ preferred ways of receiving, processing, and retaining information. Using a literature-based approach supported by empirical analysis, this study identifies practical strategies teachers can apply to improve learning effectiveness. The findings indicate that aligning teaching methods with students’ learning styles significantly enhances learning motivation, comprehension, and academic performance. Visual learners benefit from the use of images, diagrams, and written explanations; auditory learners respond well to discussions, storytelling, and verbal instruction; while kinesthetic learners achieve better understanding through hands-on activities and movement-based tasks. Implementing these strategies also fosters positive teacher–student relationships, as students feel more valued and supported when their learning preferences are acknowledged. Moreover, differentiated instruction helps create an inclusive learning environment where all students have equal opportunities to succeed. However, the article also highlights several challenges faced by teachers, including limited preparation time and insufficient training on learning-style-based pedagogy. To address these issues, the study suggests providing professional development programs, strengthening collaboration among teachers, and integrating simple yet effective techniques into classroom activities. By applying the appropriate strategies, teachers can help students reach their maximum potential and improve the overall quality of the learning experience